Antara Taklid dan Ijtihad: Dialektika Pembentukan Nalar Kritis Siswa dalam Pendidikan Islam - Suswita, Suswita (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
Contemporary Islamic education faces significant challenges in developing students’ critical thinking skills due to the dominance of the taqlīd tradition, which involves accepting teachings dogmatically without a process of in-depth reflection, thereby often limiting the space for intellectual dialectics. This condition creates a significant research gap regarding how Islamic education can transform from a pattern of passive acceptance to a more reflective and independent thinking process. This study aims to analyze the dialectic between taqlīd and ijtihād in the context of Islamic education and to formulate a philosophical approach that can foster students’ intellectual independence. Using qualitative methods through library research and hermeneutic analysis of classical and contemporary Islamic texts, as well as the thoughts of Muslim philosophers and pedagogues, this study emphasizes the importance of pedagogical ijtihād as a learning framework that opens up space for questions and answers, contemplation, and tadabbur. The results of the study indicate that an ijtihād-based approach can synthesize traditional heritage (turāṡ) with modern thought, so that students not only understand doctrinal texts textually but also can interpret their meaning and context critically and philosophically. In conclusion, the shift from passive imitation to active ijtihād in Islamic education is both an epistemological necessity and a pedagogical urgency to produce a generation of rational, autonomous, and transformative Muslims. This effort requires curriculum reform, innovation in teaching methods, and increased critical awareness of teachers as agents of change so that Islamic education can meet the challenges of the times.